International Cooperation of States in Use of Space for Shipping in the Frames of the International Programme for Search and Rescue – COSPAS-SARSAT - A. V. Lukjanova (Московский журнал международного права, 2008)
The International Programme for Search and Rescue – COSPAS-SARSAT represents a bright example of international cooperation in space and is considered to be a tried and tested model of the organization of the same cooperation for solving different problems, including solving problems concerned with safety of human life at sea In the article the following issues are considered: the activity of the COSPAS-SARSAT, the role of the COSPAS-SARSAT in regulation of states’ international cooperation in using outer space for peaceful purposes. There have been also revealed trends and perspectives of development of activity of the COSPAS-SARSAT as well as the role of the Russian Federation in the regulation of international relations in the said sphere.